Bioleaching of copper sulphide flotation concentrate in batch reaction system using mesophile and thermophile microorganisms (2012)
This work aimed at approaching the use of concentrated mesophile and thermophile microorganisms (moderate and extreme ones) in leaching process of copper sulphides flotation concentrate, containing approximately 30% of bornite (Cu5FeS4) and 70% of chalcopyrite (CuFeS2), for extracting copper. The objective of the bioleaching tests was to evaluate the performance of those microorganisms, varying specific parameters such as: the composition of leaching solution, the presence of energy source (ferrous sulphate) and the inoculation of cultures as such (controlling tests). To ensure optimal conditions for the microorganisms to act, the pH, temperature and stirring speed were controlled. Finally, from the microbial action and using agricultural fertiliser (N:P:K sources), a copper extraction of higher than 85% was achieved.